(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This study presented an experimental and theoretical study on the effect of hole on the behavior of rectangular hollow steel columns subjected to axial compression load. Specimens were tested to investigated the ultimate capacity and the load- axial displacement behavior of steel columns. In this paper finite element analysis is done by using general purpose ANSYS 12.0 to investigate the behavior of rectangular hollow steel column with hole. In the experimental work, rectangular hollow steel columns with rounded corners were used in the constriction of the specimens which have dimensions of cross section (50*80)mm and height of (250 and 500)mm with thickness of (1.25,4 and 6)mm with hole ((α*80)*80)mm when α is equal to (0.2,0.4,0.6 and 0.8). Twenty four columns under compression load were tested in order to investigate the effect of hole on the ultimate load of rectangular hollow steel column. The experimental results indicated that the typical failure mode for all the tested hollow specimen was the local buckling. The tested results indicated that the increasing of hole dimension leads to reduction in ultimate loads of tested column to 75%. The results show the reducing of load by 94.7% due to decreasing the thickness of column while the hole size is constant (0.2*80*80). The buckling load decreases by 84.62% when hole position changes from Lo=0.25L to 0.75L. Holes can be made in the middle of column with dimension up to 0.4 of column’s length. The AISC (2005) presents the values closest to the experimental results for the nominal yielding compressive strength. The effect for increasing of slendeness ratio and thickness to area ratio(t/A) leading to decreacing the critical stresses and the failure of column with large size of hole and (t/A) ratio less than 0.74% was due to lacal buckling while the global buckling failure was abserve for column with small size of hole and (t/A) ratio above than 0.74%. The compersion between the experimental and theoretical results showed a reasonable agreement and the difference was in the range (1.28-14.88)%.